2009
DOI: 10.1093/ndt/gfp362
|View full text |Cite
|
Sign up to set email alerts
|

Plasma pyrophosphate and vascular calcification in chronic kidney disease

Abstract: Plasma PPi is negatively associated with vascular calcification in end-stage renal disease (ESRD) and CKD but is not affected by dialysis, the mode of dialysis or nutritional or inflammatory status. Although these data are consistent with an inhibitory effect of PPi on vascular calcification, further studies are needed to establish a causal role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 19 publications
6
103
0
2
Order By: Relevance
“…Nevertheless, it is becoming apparent that systemic pyrophosphate levels play a key role in preventing unwanted soft tissue calcification. As already mentioned plasma pyrophosphate is reduced in patients with vascular calcification [81,82].…”
Section: Circulating Pyrophosphatesupporting
confidence: 51%
See 1 more Smart Citation
“…Nevertheless, it is becoming apparent that systemic pyrophosphate levels play a key role in preventing unwanted soft tissue calcification. As already mentioned plasma pyrophosphate is reduced in patients with vascular calcification [81,82].…”
Section: Circulating Pyrophosphatesupporting
confidence: 51%
“…Vascular calcification is particularly common in patients with advanced chronic kidney disease, where it is inversely correlated with circulating pyrophosphate levels [81,82]. Early work reported that aortic calcification was inhibited by pyrophosphate injections [83].…”
Section: Pyrophosphate and Vascular Calcificationmentioning
confidence: 99%
“…Recent studies support the hypothesis that these associations are mediated by vascular calcification (14,15), although medial calcification is seen almost exclusively in patients with advanced kidney disease and diabetes and not in the general population (16). These findings are clinically relevant because medial and intimal vascular calcification have been shown to predict cardiovascular risk in dialysis patients (17) and the general population (18).…”
mentioning
confidence: 74%
“…However, it is not clear whether ePP i levels in vessels in vivo are controlled by local activity of these enzymes rather than by systemic activity via circulating ePP i levels and whether this affects vascular calcification. Although circulating PP i levels are inversely proportional to arterial calcification in patients with advanced chronic kidney disease (14), the correlation is weak and the role of PP i metabolism in the arterial wall has never been investigated.…”
mentioning
confidence: 99%